Contribuições de uma IES pública no desenvolvimento social da região da Amesc na percepção de seus egressos - Borba, Pricila Cardoso (2020)
The aim of the study is to discuss the contributions of universities to the social development of the regions where they are located. To this end, a conceptual analysis of Amartya Sen approach to human capabilities (development as freedom) was carried out. An overview of the conceptual network of this approach is evidenced, with emphasis on issues relevant to the evaluation of educational institutions and public policies. Emphasis is placed on the roles adopted by universities, making them complex institutions, capable of contributing to the formation of the individual's agent condition, as a member of the public and as a participant in economic, social and political actions. The object of study analyzed was the Federal University of Santa Catarina, campus Araranguá, and its contributions to the development of the AMESC Region. In this sense, this research sought to identify the contributions of the installation of the Federal University of Santa Catarina in the development of the region, according to the perception of its graduates. Such understanding could reveal important elements for decision-making, be they political, economic, cultural and/or social.